HilD and PhoP independently regulate the expression of grhD1, a novel gene required for Salmonella Typhimurium invasion of host cells - Banda, María M. (2018)
When Salmonella is grown in the nutrient-rich lysogeny broth (LB), the AraC-like transcriptional regulator HilD positively controls the expression of genes required for Salmonella invasion of host cells, such as the Salmonella pathogenicity island 1 (SPI-1) genes. However, in minimal media, the two-component system PhoP/Q activates the expression of genes necessary for Salmonella replication inside host cells, such as the SPI-2 genes. Recently, we found that the SL1344-1872 hypothetical gene, located in a S. Typhimurium genomic island, is co-expressed with the SPI-1 genes. In this study we demonstrate that HilD induces indirectly the expression of SL1344-1872 when S. Typhimurium is grown in LB; therefore, we named SL1344-1872 as grhD1 for gene regulated by HilD. Furthermore, we found that PhoP positively controls the expression of grhD1, independently of HilD, when S. Typhimurium is grown in LB or N-minimal medium. Moreover, we demonstrate that the grhD1 gene is required for the invasion of S. Typhimurium into epithelial cells, macrophages and fibroblasts, as well as for the intestinal inflammatory response caused by S. Typhimurium in mice. Thus, our results reveal a novel virulence factor of Salmonella, whose expression is positively and independently controlled by the HilD and PhoP transcriptional regulators.